2018
DOI: 10.1021/acscatal.8b04219
|View full text |Cite
|
Sign up to set email alerts
|

Synergy between Ceria Oxygen Vacancies and Cu Nanoparticles Facilitates the Catalytic Conversion of CO2 to CO under Mild Conditions

Abstract: The performance of supported metal catalysts can depend on many factors, including metal particle size and dispersion and metal− support interactions, and differentiation of these effects is challenging because of their interwoven relationship. Copper/ceria catalysts are wellknown redox catalysts studied in the conversion of CO and CO 2 via oxidation and/or reduction pathways. The redox behaviors of each species, Cu-CuO and CeO x -CeO 2 , are often suggested to be interlinked, allowing ceria-supported copper d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
92
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 155 publications
(109 citation statements)
references
References 53 publications
8
92
1
Order By: Relevance
“…The copper content can significantly affect the mole fraction of Ce 3+ and Cu + species (Figure 22), and in turn, the methanol yield [306]. In addition, a space-confined synthetic approach was applied for the synthesis of highly dispersed copper-ceria catalysts for RWGS, offering 100% CO selectivity at 300 °C and ambient pressure [307]. The enhanced catalytic performance was ascribed to the abundance in interfaces formed among the highly dispersed copper nanoparticles and the Ce 3+ species, thus, favoring H2 spillover [307].…”
Section: Co 2 Hydrogenationmentioning
confidence: 99%
“…The copper content can significantly affect the mole fraction of Ce 3+ and Cu + species (Figure 22), and in turn, the methanol yield [306]. In addition, a space-confined synthetic approach was applied for the synthesis of highly dispersed copper-ceria catalysts for RWGS, offering 100% CO selectivity at 300 °C and ambient pressure [307]. The enhanced catalytic performance was ascribed to the abundance in interfaces formed among the highly dispersed copper nanoparticles and the Ce 3+ species, thus, favoring H2 spillover [307].…”
Section: Co 2 Hydrogenationmentioning
confidence: 99%
“…Reaction Promoted evidence and understanding Ref SCuCe CO 2 -to-syngas by CO 2 hydrogenation Space confined method to obtain abundant CuÀ CeO 2 interfaces by high Cu dispersion on CeO 2 , lowers CeO 2 reduction temperature and forms O vacancies, the activity even reaches equilibrium conversion [24] NiMgAl@m-SiO 2 CO 2 -to-syngas by dry reforming of CH 4…”
Section: Catalystmentioning
confidence: 99%
“…[8,[14][15][16][17][18][19][20][21][22][23] Currently, confinement catalysis has been extensively applied to the catalytic conversion of CO x regarding of improvement in catalytic activity, selectivity, and stability (Scheme 1). [9][10][11][12][24][25][26] Especially, the confined spaces of catalysts efficiently improve the catalytic selectivity for CO x conversion into fuels and high-value chemicals through the modulation of active sites and also the products self-regulation by the confined shell, which represents a promising direction for the selective conversion and utilization of carbon oxides.…”
Section: Introductionmentioning
confidence: 99%
“…Porosoff and Chen [76] compared the RWGS reaction on 1.7% Pt supported on reducible CeO 2 and irreducible Al 2 O 3 at 573 K (H 2 /CO 2 = 3/1, total pressure 30.0 Torr) and found that the forward reaction rate constant based on the mass of a catalyst and the amount of CO uptake (a measure of Pt metal dispersion) on Pt/CeO 2 are ~ 1.7 and ~ 5.7 times higher than those on Pt/Al 2 O 3 [76]. Yang et al [63] prepared ~ 2 nm Cu supported on CeO 2 and mesoporous SiO 2 to exclude the effect of the particle size of Cu. They observed that Cu/CeO x is about four times more active than Cu/SiO 2 at 573 K (Table 1; 0.2 g of catalyst, H 2 /CO 2 = 3/1, 1 bar, weight hourly space velocity of 1.08 h −1 ) and assigned this improvement to the formation of oxygen vacancies on the Cu/CeO x catalyst.…”
Section: Varying Supportmentioning
confidence: 99%
“…In summary, the activity of metal catalysts on reducible supports (CeO 2 and TiO 2 ) in a RWGS reaction is higher than that on irreducible supports (SiO 2 and Al 2 O 3 ; Table 1), but they may form more CH 4 . No CH 4 forms on Au-and Cu-based catalysts, whereas CH 4 may form on Pt and Pd catalysts [62,63]. For Pt catalysts, CH 4 selectivity is higher on reducible supports (TiO 2 and CeO 2 ) than on irreducible supports (SiO 2 and Al 2 O 3 ) possibly because of the removal of both O atoms from CO 2 by oxygen vacancies and the hydrogenation of the formed C species to CH 4 [76].…”
Section: Varying Supportmentioning
confidence: 99%